Cover Image - Lee, Wen‐Jui (Cancer Med, 2019)
The cover image is based on the Original Research Melatonin promotes neuroblastoma cell differentiation by activating hyaluronan synthase 3‐induced mitophagy by Wen‐Jui Lee et al., https://doi.org/10.1002/cam4.2389. Cover image © Yuan Soon Ho Images. [Image: see text]